Pengembangan Bahan Ajar Dan Media Pembelajaran IPAS SD/MI - Muhammad Sajudin (PEDAGOGIA : JURNAL KEGURUAN DAN PENDIDIKAN, 2025)
Learning Natural and Social Sciences (IPAS) in the Merdeka Curriculum Era requires an innovative approach. However, the practice in the field is still dominated by conventional methods that do not involve students. This study aims to develop and test the feasibility and effectiveness of integrated learning packages that combine project-based teaching materials with media augmented reality (AR) for elementary/MI students. This study uses research and development methods (R&D) with a systematic ADDIE model. Research data sources involve material experts, media experts, class V teachers, and grade V SD/MI students as research and trial subjects. The results showed that the IPAS-PROAR learning package developed was declared very feasible by the expert validator and was very practical for use by teachers and students based on the response questionnaire analysis. Furthermore, the product is proven to be significantly effective in improving student learning outcomes, which is demonstrated by the achievement of the average N-Gain Score in the high category. This finding implies that the integration of project-based pedagogy with AR technology is a potential solution to create active, meaningful, and in accordance with the demands of 21st-century skills.